A post-processing module based on Cressman's analysis to improve the Wind Energy Simulation Toolkit mapping system. Issue 3 (June 2019) - Alonso, Yoandy; Martinez, Yosvany; Roque, Alfredo; Yu, Wei; Borrajero, Israel
In this work, a post-processing module based on Cressman's method of objective analysis is added to the Wind Energy Simulation Toolkit in order to improve the accuracy of the numerical wind atlas of Cuba. Mean wind speed surface observations at 35 meteorological stations and mean wind speed observations at 10, 30, 50, and 100 m height above ground level collected at a network of 58 observation towers are assimilated in the Cressman analysis. Furthermore, the 3-year numerical wind atlas generated for the same period of time is considered as the first guess for the Cressman method. A new wind atlas of Cuba is generated and verified using observation records at 32 meteorological stations and 10 observation towers distributed over the country. In addition, the capability of the new post-processing scheme to adding information on the temporal variability of the wind resource is explored.